2018
DOI: 10.1155/2018/5897381
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Ampicillin Surface Molecularly Imprinted Polymers for Its Selective Recognition of Ampicillin in Eggs Samples

Abstract: Surface-imprinted polymers (MIPs) microspheres with the ability to specifically recognize water-soluble molecules were prepared using self-made monodisperse porous poly(chloromethylstyrene-co-divinylbenzene) beads as the solid-phase matrix and ampicillin (AMP) as the template molecule. MIPs were synthesized using different template molecule: monomer: crosslinker ratios and the optimum preparation ratio were obtained by measuring adsorption. The maximum equilibrium amount of adsorption by the MIPs reached 115.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…38 This difference in pore size has also been linked to the high specific surface area and binding amount observed for MIPs. 38,39 Furthermore, studies on surface morphology using SEM have shown remarkable difference between MIPs and NIPs, whereby MIPs have demonstrated a highly porous surface (Figure 3), which has been attributed to formation of selective cavities within the polymer matrix.…”
Section: Ifmentioning
confidence: 99%
See 1 more Smart Citation
“…38 This difference in pore size has also been linked to the high specific surface area and binding amount observed for MIPs. 38,39 Furthermore, studies on surface morphology using SEM have shown remarkable difference between MIPs and NIPs, whereby MIPs have demonstrated a highly porous surface (Figure 3), which has been attributed to formation of selective cavities within the polymer matrix.…”
Section: Ifmentioning
confidence: 99%
“…In terms of pore size distribution, there are reported differences between MIPs and NIPs at both the macropore and mesopore region, where MIPs display a higher population than NIPs, which has been attributed to the template effect (Figure 2). 38 This difference in pore size has also been linked to the high specific surface area and binding amount observed for MIPs 38,39 …”
Section: Molecular Imprinting Processmentioning
confidence: 99%
“…The applications of MISPE and MIP sensors for the analytical determination of antibiotic residues are comprehensively reviewed according to the different kinds of SAs, QNs, BALs, MALs, TCs, AGs and others. Some typical examples of MISPE in antibiotic analysis are listed in Table 1 [10,11,23,40,42,45,49,51,56,59,[78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95], and MIP-based electrochemical sensors and optical sensors for antibiotic analysis are shown in Table 2 [68][69][70]72,[96][97][98][99][100][101][102][103][104][105][106][107] and Table 3 [74,76,…”
Section: Applications Of Mips For Antibiotic Analysismentioning
confidence: 99%
“…Amoxicillin (Amo) is a common aminopenicillin. Usually, one can obtain it semi-synthetically from natural penicillin [8]. To date, it is the most prescribed antibiotic for children [9,10].…”
Section: Introductionmentioning
confidence: 99%